Аssessment of the risk of the consumption of drinking water with the increased content of nitrates for the health of the people of the Ternopil oblast - Lototska О.V.; Prokopov V.О. (Environment & Health, 2018)
Objectives: We calculated the risk ratio and assessed the risk of impact of drinking water with an increased content of nitrates on the health of the population in various regions of the Ternopil oblast. Materials and methods: We used the results of the monitoring of the compliance with the standards of drinking water quality indicators from decentralized sources by sanitary and chemical indicators in the Ternopil oblast obtained at the State Institution "Ternopil Regional Laboratory Center of the Ministry of Health of Ukraine". We used the data from the Information and Analytical Center for Medical Statistics in the Ternopil Oblast for 2010 and 2016 years. To achieve this goal, we applied hygienic, analytical, and statistical research methods. Results: There is a clear tendency to a significant number of deviations by sanitary and chemical indicators of water quality in nitrate content in the south and south-eastern parts of the Ternopil oblast. The assessment of the risk factor of the consumption of drinking water, contaminated with nitrates, in the Borshchevskyi, Zalishchytskyi and Chortkivskyi regions indicates a risk of the increase of non-infectious morbidity, especially for sensitive groups of the population. The results of the calculation of non-carcinogenic risk at the intake of nitrates with drinking water up to 2 MPCs showed that the quantity of the risk in all regions complied with the average risk and grew with an increase of their concentration in water. The probability of the development of the hazardous effects for the children is higher in all regions where consuming water has the same content of nitrates, the higher HQ indices indicate it. The high risk of the adverse effects in the most children is possible at the content of nitrates of 3-7 and more MACs in two regions of the Ternopil oblast – the Borshchevskyi and Zalishchytskyi ones. Estimation of the population health of the population in these regions with the help of demographic indicators showed that recent years mortality exceeds the birth rate. Conclusions. Thus, negative tendencies are noted in the health status of the population of the Ternopil region. In connection with this, it is necessary to develop and carry out urgent measures to prevent further contamination of underground sources of drinking water with nitrates and to prevent its negative impact on the health of the population.